Prediction of Net Returns from Apple (Malus Domestica Borkh.) In Kashmir From Some Agro-economic And Socio-personal Correlates - S. K Acharjee; W. Qadri; A. Haque (Journal of Agricultural Extension Management, 2025)
The horticultural sector has established its credibility for augmenting the productivity of land, generating employment and, above all, providing nutritional security especially for those who need it the most production and management of apple in Kashmir has gone imbued. A mi x of traditionally and modernity breeds on vacillating and hesitating approach in ensuring application of modern but risk pro ne, di verse but complex package of practice